2006
DOI: 10.1002/humu.20344
|View full text |Cite
|
Sign up to set email alerts
|

Reduced secretion of fibulin 5 in age-related macular degeneration and cutis laxa

Abstract: Age-related macular degeneration (ARMD) is the leading cause of irreversible visual loss in the Western world, affecting approximately 25 million people worldwide. The pathogenesis is complex and missense mutations in FBLN5 have been reported in association with ARMD. We have investigated the role of fibulin 5 in ARMD by completing the first European study of the gene FBLN5 in ARMD (using 2 European cohorts of 805 ARMD patients and 279 controls) and by determining the functional effects of the missense mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 38 publications
3
66
0
2
Order By: Relevance
“…The primary cause of vision loss in AMD is choroidal neovascularization, which is characterized by abnormal angiogenesis of the choroidal vasculature through Bruch's membrane. This neovascularization is mediated by VEGF, and it is therefore intriguing that some fibulin-5 missense mutations may alter the regulation of VEGF by fibulin-5, either by reduced fibulin-5 secretion (Lotery et al, 2006) or by reduced affinity of fibulin-5 and VEGF, leading to unregulated blood vessel growth.…”
mentioning
confidence: 99%
“…The primary cause of vision loss in AMD is choroidal neovascularization, which is characterized by abnormal angiogenesis of the choroidal vasculature through Bruch's membrane. This neovascularization is mediated by VEGF, and it is therefore intriguing that some fibulin-5 missense mutations may alter the regulation of VEGF by fibulin-5, either by reduced fibulin-5 secretion (Lotery et al, 2006) or by reduced affinity of fibulin-5 and VEGF, leading to unregulated blood vessel growth.…”
mentioning
confidence: 99%
“…Four variants (Gly412Glu, Gly267Ser, Ile169Thr, Gln124Pro) in fibulin-5 that have been associated with AMD dramatically reduce the protein's secretion, and a similar effect was observed for mutations that have been linked to cutis laxa, a rare connective tissue disorder that is characterized by loose, sagging, inelastic skin that can present together with developmental emphysema and major defects in the systemic and pulmonary arteries (Lotery et al 2006;Schneider et al 2010). The Gly412Glu variant causes aggregation of the protein (Jones et al 2010), and the Gly267Ser variant causes extensive misfolding (Schneider et al 2010), which may explain the reduced secretion of these mutant proteins.…”
Section: Fibulin-5 (Fbln5)mentioning
confidence: 74%
“…Interestingly, several patients carrying rare variants in the CFH, CFI, and FBLN5 genes have been reported to have cuticular drusen (Stone et al 2004;Lotery et al 2006;Boon et al 2008Boon et al , 2013van de Ven et al 2012a). This clinical subtype of AMD presents at an earlier age than typical AMD, has a strong familial component, and it has been proposed that genetic factors may play a more important role in its development than in the general AMD population (Grassi et al 2007;van de Ven et al 2012b;Boon et al 2013).…”
Section: Recognition Of Clinical Subtypes Of Amdmentioning
confidence: 99%
“…24) Lotery et al revealed that fibulin-5 secretion was significantly reduced for 4 age-related macular degeneration (p.G412E, p.G267S, p.I169 T, and p.Q124P) and 2 cutis laxa (p.S227P, p.C217R) mutations. 25) They showed that some missense mutations lead to decreased fibulin-5 secretion with a possible corresponding reduction in elastinogenesis. To clarify the mechanism of reduction in fibulin-5 protein, we performed sequence analysis of fibulin-5.…”
Section: Discussionmentioning
confidence: 99%